Analysis of Novel Metastasis‐associated Gene TI‐227 - Ishiguro, Tatsuaki (Jpn J Cancer Res, 2000)
TI‐227, is a cancer metastasis‐associated gene isolated from the B16‐F10 mouse melanoma subline that preferentially metastasizes to the lung following intravenous injection. TI‐227, is more highly expressed in the B16‐F10 and colon26‐n117 sublines, which preferentially metastasize to the lung following intravenous injection, than in the B16‐BL6 and colon26‐nl22 sublines, which preferentially metastasize to the lung following subcutaneous injection. Since TI‐227, could not be detected in normal tissues, there is a possibility that it is expressed specifically in tumors that preferentially metastasize to the lung following intravenous inoculation. Although the 5’ end of TI‐227 was analyzed, its total sequence contained no obvious open reading frame. However comparison with the isolated human counterpart, TI‐227H, gene, revealed a highly homologous region near the 3’ end, which was expected to contain a very short open reading frame.